Process optimization for xylitol purification using liquid-liquid batch extraction : effect of volume ratios and number of stages - Wai Mun, Low (2015)
Xylitol is a five-carbon sugar alcohol that has many significant applications in the food, and pharmaceutical industries owing to its unique properties. Xylitol has proven its core value in reducing tooth decay and as sugar substitute for diabetes patient. In general, purification steps for production of fine product are of great interest in process engineering due to the complexity of the separation processes which leads to the major costing in production. Liquid-liquid extraction is a simple, time and energy saving separation method that employed to separate xylitol and impurities. Objective of this research is to optimize the conditions for purification of xylitol with ethyl acetate as solvent using response surface methodology in batch solvent extraction. Experiment design were done with one factor at time method to screen the significance of various factors, then RSM analysis was performed and experiments was conducted based on the suggested models. All the experiments were done in three replications to minimize systematic and instrument errors. OFAT results had shown that the time of extraction is not significant but the optimum conditions for volume ratio of sample to solvent is 1:5, and the number of multiple staging are 5 stages. Henceforth in RSM analysis, first factor was set to be the volume ratio of sample to solvent ranging from 1:2 to 1:6 and second factor was set to be the number of staging ranging from 2 to 6 stages. RSM analysis results that the overall model is valid, with correlation p-value of 0.002 (<0.05) with both two factors and factors’ squared proven to be significant to the response. The lack of fit value of 0.0003 for the model is significant. Feasibility study which is the xylitol extraction optimization using above suggested model by RSM produced from Meranti wood is validated. Results obtained from this research have demonstrated that both volume ratio and number of stages have significant effects in extraction process of xylitol purification and through careful optimization the downstream processing of commercial xylitol could be more effective